Regulation of Antigen 43, a phase-variable autoaggregation factor of Escherichia coli - Waldron, Denise Ethel (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2003)
The Antigen 43 protein (Ag43) of Escherichia coli, encoded by the agn43 gene, has previously been shown to be expressed in a phase-variable manner. A plasmidborne fusion of the agn43 regulatory region to the reporter gene lacZ, was constructed and used to study the regulation of Ag43 at the level of transcription. Pgalactosidase expression, under the control of the agn43 promoter was phasevariable in a background containing functional OxyR and Locked ON in an oxyR mutant, confirming that Ag43 phase variation is regulated, by OxyR, at the transcriptional level. In an oxyR, Locked ON background, the agn43 promoter was induced in the stationary phase of growth, and was regulated in response to the environmental cues of temperature and oxygen availability.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin